2018
DOI: 10.1016/j.ymgmr.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Living with phenylketonuria in adulthood: The PKU ATTITUDE study

Abstract: Dietary treatment is the cornerstone of therapy for phenylketonuria (PKU), but adherence to low- phenylalanine diet progressively decreases after adolescence. We designed a survey to characterize the dietary habits of Italian adult PKU patients and to identify psychological factors influencing disease perception and adherence to diet. Participants to the survey (n = 111; response rate 94%) were asked to complete a structured questionnaire. Patients appeared to have an altered perception and awareness of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 30 publications
6
81
0
Order By: Relevance
“…2 Without PAH function, chronic untreated hyperphenylalaninemia causes severe neurological damage, leading to intellectual disability, psychological disorders, and seizures. 1,3 It is important to note that human clinical PKU phenotypes form a disease continuum, ranging from mild hyperphenylalaninemia (blood Phe = 120-600 mM) to mild PKU (blood Phe = 600-1200 mM), to the most severe, classical PKU (cPKU) (blood Phe > 1200 mM), depending upon the amount of residual liver PAH activity in the patient. Due to the severity of largely preventable neurological symptoms, all infants born in medically advanced countries undergo newborn screening for hyperphenylalaninemia and are placed on dietary treatment early in life.…”
Section: Introductionmentioning
confidence: 99%
“…2 Without PAH function, chronic untreated hyperphenylalaninemia causes severe neurological damage, leading to intellectual disability, psychological disorders, and seizures. 1,3 It is important to note that human clinical PKU phenotypes form a disease continuum, ranging from mild hyperphenylalaninemia (blood Phe = 120-600 mM) to mild PKU (blood Phe = 600-1200 mM), to the most severe, classical PKU (cPKU) (blood Phe > 1200 mM), depending upon the amount of residual liver PAH activity in the patient. Due to the severity of largely preventable neurological symptoms, all infants born in medically advanced countries undergo newborn screening for hyperphenylalaninemia and are placed on dietary treatment early in life.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effluents discharged by these industries contain untreated dyes which can be toxic to human beings and aquatic life and hence their removal from contaminated wastewater is essential. Various methods such as adsorption over activated carbon (Wen et al, 2016), thermolysis, and coagulation (Yen et al, 2017), membrane separation (Cazzorla et al, 2018;Ye et al, 2018), electrochemical decolorization (Xu L. et al, 2018), photocatalytic degradation (Liu et al, 2019), and biological treatment (Banihani et al, 2018) have been widely reported for the removal of organic pollutants. Among these methods, adsorption over activated carbon is envisaged as highly effective technique.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of participants (75%) were noncompliant as evidenced by plasma PHE levels >360 μmol/L, which reduced the size of the compliant subgroup for our analysis. Unfortunately, high numbers of noncompliance with plasma PHE and diet requirements, particularly among adolescents and adults, are common in the PKU medical population . Another limitation was that plasma tryptophan could not be calculated into the sum of plasma LNAA concentrations in 14 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, high numbers of noncompliance with plasma PHE and diet requirements, particularly among adolescents and adults, are common in the PKU medical population. [31][32][33][34] Another limitation was that plasma tryptophan could not be calculated into the sum of plasma LNAA concentrations in 14 cases. This may have affected the sum of the plasma LNAA concentration values and the significance of associations in the analysis.…”
Section: Discussionmentioning
confidence: 99%